De-romanticising critical marketing theory: capitalist corruption as the Left's Žižekean fantasy. Issue 1 (2nd January 2022) - Coffin, Jack; Egan-Wyer, Carys
ABSTRACT: Following Slavoj Žižek, critical marketing scholars have interrogated the ideological fantasies of mainstream marketing, de-romanticising markets and marketing. However, Žižek argues there is no ideology-free subject, so it stands to Žižekean reason that critical marketing scholars are also ideological fantasists. Our paper seeks to de-romanticise critical marketing theory by identifying the fantasy of capitalist corruption. This sustains the ideology of critical marketing theory by disavowing (self-)destructive desires within the human unconscious and suggesting that displacing capitalism will be enough to usher in a postcapitalist utopia. This ideological fantasy has therapeutic, motivational, and institutional benefits, but romanticises the human subject in ways that ultimately frustrate the critical project of societal betterment. By acknowledging the human unconscious as a corrupting influence, we hope to make critical aspirations more likely to be realised. We illustrate our argument via studies of sustainability, a favoured topic of Žižekean, critical, and mainstream scholars alike.